2014
DOI: 10.1177/0022034514557331
|View full text |Cite
|
Sign up to set email alerts
|

Proresolving Nanomedicines Activate Bone Regeneration in Periodontitis

Abstract: Therapies to reverse tissue damage from osteolytic inflammatory diseases are limited by the inability of current tissueengineering procedures to restore lost hard and soft tissues. There is a critical need for new therapeutics in regeneration. In addition to scaffolds, cells, and soluble mediators necessary for tissue engineering, control of endogenous inflammation is an absolute requirement for success. Although significant progress has been made in understanding natural resolution of inflammation pathways to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 36 publications
2
103
0
1
Order By: Relevance
“…Along these lines, NPRM containing a novel lipoxin analog (benzo-lipoxin A 4 , bLXA 4 ) promote hard and soft tissue regeneration in periodontitis in the Hanford miniature pig. NPRM-bLXA 4 markedly reduces inflammatory cell infiltrate into chronic periodontal disease sites and increases new bone formation [44]. These findings offer a new therapeutic tissue-engineering approach for the treatment of chronic osteolytic inflammatory diseases.…”
Section: Microparticles and New Players In Local Spm Biosynthesismentioning
confidence: 99%
“…Along these lines, NPRM containing a novel lipoxin analog (benzo-lipoxin A 4 , bLXA 4 ) promote hard and soft tissue regeneration in periodontitis in the Hanford miniature pig. NPRM-bLXA 4 markedly reduces inflammatory cell infiltrate into chronic periodontal disease sites and increases new bone formation [44]. These findings offer a new therapeutic tissue-engineering approach for the treatment of chronic osteolytic inflammatory diseases.…”
Section: Microparticles and New Players In Local Spm Biosynthesismentioning
confidence: 99%
“…Animals models of periodontal disease have been used to demonstrate regeneration of periodontal tissues mediated by lipoxins and resolvins, endogenous regulators if inflammation (8, 54, 94). The capacity for regeneration in small animals is greater than in large animals and man.…”
Section: Pro-resolving Mediators In Periodontal Regenerationmentioning
confidence: 99%
“…Large animals spontaneously develop periodontitis, like in humans, and do not spontaneously regenerate periodontal tissue under any circumstances, again, like humans. Thus, to more replicate the treatment of periodontal disease in humans, a lipoxin analog was used as an adjunct to periodontal surgical therapy to evaluate the impact on periodontal regeneration (94). Using the Hanford Miniature Swine with chronic periodontitis, surgical debridement of the periodontal lesion was followed by placement of lipoxin analog in a neutrophil microparticle carrier in the lesion before suturing.…”
Section: Pro-resolving Mediators In Periodontal Regenerationmentioning
confidence: 99%
“…In an experimental model of periodontitis, RvE1 prevented chronic inflammation, tissue breakdown and resulted in wound healing with restoration (regeneration) of all lost tissues [22, 27] suggesting a major role in regulating wound healing and regeneration. These observations have been further supported using lipoxins in a large animal model of regeneration [28]. In diabetic wound healing, Tang et al demonstrated that RvD1 enhances wound closure in mice with decreased accumulation of apoptotic cells, macrophages and the susceptibility to infection [29].…”
Section: Introductionmentioning
confidence: 95%